2015
DOI: 10.1097/phm.0000000000000171
|View full text |Cite
|
Sign up to set email alerts
|

Role of Electrical Stimulation Added to Conventional Therapy in Patients with Idiopathic Facial (Bell) Palsy

Abstract: The addition of 3 wks of daily electrical stimulation shortly after facial palsy onset (4 wks), improved functional facial movements and electrophysiologic outcome measures at the 3-mo follow-up in patients with Bell palsy. Further research focused on determining the most effective dosage and length of intervention with electrical stimulation is warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
53
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(57 citation statements)
references
References 12 publications
0
53
0
4
Order By: Relevance
“…So far only a few longitudinal studies, mostly with small sample sizes, have been published using the FDI or the FaCE before, during, and after therapy of patients with FP . Recently, the first large series of 148 patients was presented using the FaCE score to evaluate quality of life prior to and after free gracilis muscle transfer for smile restoration .…”
Section: Introductionmentioning
confidence: 99%
“…So far only a few longitudinal studies, mostly with small sample sizes, have been published using the FDI or the FaCE before, during, and after therapy of patients with FP . Recently, the first large series of 148 patients was presented using the FaCE score to evaluate quality of life prior to and after free gracilis muscle transfer for smile restoration .…”
Section: Introductionmentioning
confidence: 99%
“…This was also supported by Tucany et al who noted that the addition of Electrical Stimulation to physical therapy and corticosteroids significantly improved House-Brackmann scores in subjects with acute Bell's palsy [14]. And LM Pereira et al who performed a systematic review & found Facial exercise therapy is effective for facial palsy for the outcome functionality [12].…”
Section: Methodsmentioning
confidence: 80%
“…In a randomized, controlled trial, Tuncay et al reported positive effects in patients with Bell palsy and repetitive ES during the time of spontaneous recovery . The treatment group received ES beginning in the fourth week of acute palsy for 3 weeks with monophasic pulses of 100 milliseconds, a pulse interval of 300 milliseconds, at a rate of 2.5 Hz, until muscle contraction was visible.…”
Section: Discussionmentioning
confidence: 99%
“…Kern et al showed in computed tomography scans and histology of muscle biopsies that ES improved muscle mass and structure 3. In our study, we have provided no quantitative outcome measures of muscle morphology.In a randomized, controlled trial, Tuncay et al reported positive effects in patients with Bell palsy and repetitive ES during the time of spontaneous recovery 30. The treatment group received ES beginning in the fourth week of acute palsy for 3 weeks with monophasic pulses of 100 milliseconds, a pulse interval of 300 milliseconds, at a rate of 2.5 Hz, until muscle contraction was visible.…”
mentioning
confidence: 99%